Taxpayer Evasion Strategies for Tax Evasion after Demonetization (International Journal of Food and Nutritional Sciences, 2022)
Tax reform is a complex and evolving process that involves strategic changes to a country's tax system to enhance its efficiency, fairness, and overall effectiveness. These changes can range from modifying tax rates and structures to revamping administrative procedures and introducing new tax policies. The main goals of tax reform usually include optimizing revenue collection, stimulating economic growth, and ensuring a fair distribution of the tax burden among individuals and businesses.This study focuses on analyzing the significant tax reforms in India following demonetization, highlighting their intricacies and effectiveness. It also assesses the actual tax revenue generated by the government, providing insights into the fiscal outcomes of these reforms. By thoroughly examining these aspects, the study aims to offer valuable insights into the evolving taxation landscape in India and its implications for the broader economy.